The effectiveness comparison between letrozole and clomiphene citrate as ovulation induction therapy in patients of polycystic ovarian syndrome (PCOS) - Putri Dhiya Prameswari Wiyono (Science Midwifery, 2023)
Letrozole is an aromatase inhibitor that has been tested and proven to be superior to CC in terms of ovulation, pregnancy and birth rates. However, letrozole has the potential to be teratogenic to the fetus. To compare the effectiveness of Letrozole and Clomiphene Citrate as ovulation induction therapy in polycystic ovarian syndrome (PCOS) patients. Methods is Literature review of four databases; PubMed, DOAJ, Cochrane, and Google Scholar published within the last 5 years from 2018-2022. There were 11 studies reporting the effectiveness of Letrozole and Clomiphene Citrate as ovulation induction therapy in polycystic ovarian syndrome (PCOS) patients. Primary and secondary outcomes are used to evaluate outcomes. The key outcomes were the drug's impact on ovulation, birth, pregnancy, multiple pregnancies, miscarriages, and birth defects rates. The effectiveness of combination therapy and monotherapy was also contrasted in this literature study. Based on this literature review, it was found that Letrozole is superior to Clomiphene Citrate as an ovulation induction agent in PCOS patients. Letrozole is also associated with a better probability of pregnancy and birth and a lower chance of multiple pregnancies. The probability of miscarriage and the occurrence of congenital anomalies or defects in the newborn did not differ between the groups receiving letrozole or CC. In addition, the combination of letrozole and CC was superior to letrozole alone in increasing the ovulation rate in women with PCOS. Letrozole is also better and more acceptable than the combination of CC and metformin for inducing ovulation.